FEATURES OF ELECTRIC MOTOR CHOICE FOR NUCLEAR POWER PLANT TECHNOLOGICAL OBJECTS - Pavlenko, T. P.; Shevchenko, V. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2013)
Nuclear power plants remain the basic power generating enterprises for Ukraine. Execution of works on their reliability control and operating conditions optimization is therefore of current importance. Trouble-free nuclear power plant operation is a vital technical, economical, and ecological problem, a solution to which is largely specified by reliable operation of electric equipment, namely, electric motors of nuclear power plant technological process drives.